A brain-computer interface based on the integration of NI myRIO development device and NeuroSky Mindwave headset - Ruşanu, O A; Cristea, L; Luculescu, M C; Cotfas, P A (IOP Publishing, 2018)
This paper describes the development of a brain-computer interface system used for controlling a mobile robot by the eye-blinks strength. This project is aimed to help people with neuromotor disabilities who suffered from severe diseases causing them paralysis or the loss of speech. The proposed solution is related to the integration of NI myRIO platform with a NeuroSky Mindwave electroencephalographic headset in order to provide them an efficient, precise and robust communication channel with the outside environment. The eye-blinks are artefacts similar to the spikes that can be observed into the electroencephalographic signal. The difference between an intentional and a reflexive eye-blink is identified through the comparison of its strength to a given threshold parameter. Further, this paper describes a LabVIEW based application developed on the three programming levels from the NI myRIO (My Computer, Real-Time, FPGA Target) which enables controlling a mobile robot by different movement directions using the total number of voluntary eye-blinks. Therefore, the patient is able to use eye-blinks in order to send to the assistive device the following commands: stop – one eye-blink, go forward – two eye-blinks, go backward – three eye-blinks, turn left – four eye-blinks and turn right – five eye-blinks.